Computational approach against milk allergy for hypersenstivity and malnutrition in newborn (Funded Work) - IFTIKHAR ASLAM TAYUBI (International Journal of Pharma and Bio Sciences, 2017)
The growth and development of a newborn largely depends on the nutrient content of mother’s milk as diet intake. Milk is regarded as one of the most essential parts of a healthy diet in almost all over the world. It is the major source of all the nutrients required, especially to the neonates and infants for normal development. Cow milk is the second best source of nutrition for infants. Having said that, up to 6% children are unable to digest cow milk for those suffering from the hypersensitivity reaction, which is the reason for the CMA (Cow Milk Allergy). CMA leads to the necessity of an alternative to cow milk. In such case, sheep milk is regarded as the second possibility. Looking at the scenario where human, cow and sheep’s milk are simultaneously required in a population; we study on the content analysis of each milk sample. The contents of various sources of milk for fibronectin, lactoferrin, lysozyme and alpha casein S1 protein were analyzed to identify the protein structure, functions and evolution of the concerned protein families. Further, the protein constituents with physical and chemical parameters for each protein were studied. The secondary structures were especially studied in this protein analysis for a higher level of understanding. The analysis from the study shows that the cow milk has better advantage of essential amino acids as compared to the human and sheep’s milk. The current study shows remarkable results with greater similarity in terms of sequence identity and amino acid content of proteins in human and sheep milk as compared to the cow milk.